ANALISIS SISTEM PENGELOLAAN PIUTANG MURABAHAH PADA LEMBAGA KEUANGAN SYARIAH - Waluyo, Waluyo; Nugroho, Afif Khairy; Fita Emiliana, Putri Diana; Rahmawati Solehah, Berliana; Khoirunissa Haryanto, Najwa Hanifah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study analyses the receivables management system in Mudharabah financing in Sharia Financial Institutions (LKS) in Indonesia which has grown rapidly in recent years. Referring to the principle of people's economy in the 1945 Constitution, Islamic financing is a banking activity that involves collecting funds from the public such as giro, savings, deposits, to be channeled back to the community through financing or credit schemes. This research explores the effectiveness of the receivables management system, particularly in relation to the murabahah contract-a commonly used contract that is prone to risks, such as Non Performing Financing (NPF). This study uses the literature method to analyse the concept of murabahah, including its pillars, types, implementation in Islamic banking, as well as its influencing factors, including third-party funds (DPK) and profit margins. The results of the analysis are expected to provide a comprehensive picture of the management of Mudharabah receivables in Islamic financial institutions and identify potential efficiency improvements, in line with sharia principles and the context of the Indonesian economy based on the principle of kinship.